The Effect of Professional Development Programs on Improving Teaching Performance Among Arabic Teachers in Nigeria - Garba, Ahmad (Indonesian Journal of Pedagogy and Teacher Education, 2024)
This research aims to explain the impact of training or professional development for teachers during their service, and the extent to which this is permitted in developing human resources in the workplace. The teaching profession, like other professions, needs to develop and improve the skills of its members to increase the effectiveness of their performance and carry out their roles optimally. Vocational training is part of achieving the goals of the educational process. For example, teachers need to update their knowledge and skills to develop students' abilities. Therefore, the development of professional qualitative programs serves to provide modern knowledge and advanced skills, as well as ensuring their application and integration into classroom activities. In this context, individual differences between teachers are taken into account in several aspects according to their level of experience and professional qualifications. It also pays special attention to the psychological needs of some school members, represented in the desire to support their peers and give them feedback, and the need for some teachers to participate effectively in developing their school. Due to the nature of research, researchers use a descriptive approach to obtain scientific information and material related to the subject. The research results concluded that professional development programs and their types had a positive impact on teacher development performance during their service.